Micro Structural Study of Plasma-sprayed Zirconia-CaO Thermal Barrier Coatings. (2015) - Imran, A.; Alam, S.; Irfan, M.; Farooq, M.
Abstract: Zirconia (ZrO2 ) coating synthesized by plasma spray method is widely used industrially as a thermal barrier coating (TBC), showing problems such as spallation and cracks inside the coatings. The coatings are subjected to cyclic temperature fields which result in thermal expansion while heating and shrinkage during cooling. Thus the coating should be strain-tolerant. The bond coat contains oxide forming elements, i.e. aluminum (Al) and chromium (Cr) which are converted into Al2 O3 and Cr2 O3 at high temperatures & provide a good protection against further oxidation. On the other hand, it was found that the lifetime of TBC with stabilized zirconia overlay is reduced by the wear resulting from different chemical reactions. Present work was aimed on study of calcia (CaO) stabilizers in zirconia TBC. For experimentation the samples were selected with adjustable controlling parameters to produce TBC with CaO stabilizer effect with Ni 5%Al as bond coat. Then the complete characterization was done to optimize the microstructural, topography of these coatings by using the latest techniques. The results depict that CaO has shown more promising application in TBC.